Impact of body mass index on survival after colorectal cancer diagnosis: the Cancer Prevention Study-II Nutrition Cohort - Campbell, Peter T; Newton, Christina C; Dehal, Ahmed N; Jacobs, Eric J; Patel, Alpa V; Gapstur, Susan M (Journal of clinical oncology, 2012)
The impact of body mass index (BMI) on survival after colorectal cancer diagnosis is poorly understood. This study assessed the association of pre- and postdiagnosis BMI with all-cause and cause-specific survival among men and women diagnosed with colorectal cancer in a prospective cohort. Participants in the Cancer Prevention Study-II Nutrition Cohort reported weight and other risk factor information via a self-administered questionnaire at baseline in 1992 to 1993. Updated information on current weight and incident cancer was reported via periodic follow-up questionnaires. This analysis includes 2,303 cohort participants who were diagnosed with nonmetastatic colorectal cancer between baseline and mid 2007 and were observed for mortality from diagnosis through December 2008. A total of 851 participants with colorectal cancer died during the 16-year follow-up period, including 380 as a result of colorectal cancer and 153 as a result of cardiovascular disease (CVD). In analyses of prediagnosis BMI (weight reported at baseline in 1992 to 1993; mean, 7 years before colorectal cancer diagnosis), obese BMI (≥ 30 kg/m(2)) relative to normal BMI (18.5 to 24.9 kg/m(2)) was associated with higher risk of mortality resulting from all causes (relative risk [RR], 1.30; 95% CI, 1.06 to 1.58), colorectal cancer (RR, 1.35; 95% CI, 1.01 to 1.80), and CVD (RR, 1.68; 95% CI, 1.07 to 2.65). Postdiagnosis BMI (based on weight reported; mean, 1.5 years after diagnosis) was not associated with all-cause or cause-specific mortality. This study suggests that prediagnosis BMI, but not postdiagnosis BMI, is an important predictor of survival among patients with nonmetastatic colorectal cancer.